PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN MENERAPKAN TIPE TALKING STICK DI SEKOLAH DASAR - Ferdiani, Elly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This study aimed to describe the learning outcome of students in the learning of Sciences adopted different types of talking stick Elementary School fourth grade 01 South Pontianak. The method used in this research is descriptive method. This research was conducted as much as two cycles each cycle two meetings. The results obtained are: (a) the ability of teachers write lesson plans first cycle of the first meeting on average 2,73, 2 meeting an average of 3.06, second cycle of the first meeting of an average of 3.36, the average meeting 2 3 , 63. (B) the ability of teachers to implement the first meeting of the first cycle of learning an average of 2.47, 2 meeting average of 3.10, second cycle of the first meeting on average 3.50, 2 meeting average of 3.68. (C) the results of study for students from the first cycle of the first meeting on average 67.78, meeting II average of 76.67, second cycle of the first meeting on average 82.22, 2 average meeting 86.56. This indicates that the application of the type of talking stick can improve learning outcomes fourth grade students of State Elementary School 01 South Pontianak.Â Keywords: Enhancement, Learning Outcomes, Social Sciences, Type Talking Stick Â